2015
DOI: 10.1088/1741-2560/12/6/066022
|View full text |Cite
|
Sign up to set email alerts
|

Sensor fusion and computer vision for context-aware control of a multi degree-of-freedom prosthesis

Abstract: The CASP constitutes a substantial improvement for the control of multi-DOF prostheses. The application of the CASP will have a significant impact when translated to real-life scenarious, particularly with respect to improving the usability and acceptance of highly complex systems (e.g., full prosthetic arms) by amputees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 55 publications
(60 reference statements)
2
87
0
Order By: Relevance
“…These workaround techniques have emerged mainly because the promised EMG pattern recognition-based methods have not proved robust, or even feasible, for grasp classification clinically. The non-intuitiveness and shortcomings of the aforementioned approaches have encouraged the emergence of techniques that advocate utilisation of sensing modalities other than the conventional EMG signals, such as accelerometry or in general inertial measurements [14,25,26,57], RFID tags [28], artificial vision including standard cameras as well as Kinect [29][30][31][32][33][34]. In almost all multi-modal approaches to control limb prosthesis, it is argued that the incorporation of two or more sources of information can reduce the users' cognitive burden and enhance functionality in terms of accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These workaround techniques have emerged mainly because the promised EMG pattern recognition-based methods have not proved robust, or even feasible, for grasp classification clinically. The non-intuitiveness and shortcomings of the aforementioned approaches have encouraged the emergence of techniques that advocate utilisation of sensing modalities other than the conventional EMG signals, such as accelerometry or in general inertial measurements [14,25,26,57], RFID tags [28], artificial vision including standard cameras as well as Kinect [29][30][31][32][33][34]. In almost all multi-modal approaches to control limb prosthesis, it is argued that the incorporation of two or more sources of information can reduce the users' cognitive burden and enhance functionality in terms of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Skin movement analysis via accelerometry signals [25,26], force myography [27], use of radio-frequency identification (RFID) tags [28], arm movement trajectory and inertial measurement (e.g. i-mo TM ) and computer vision [29][30][31][32][33][34] are some examples. Specifically, in the case of using computer vision, it was shown that object shapes can be quantised such that appropriate grasp types and sizes can be determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods are useful in simple and short tasks. However, as the number of functions increases, more time is needed to select the intended function [4,5]. Cocontraction switching is commonly used for switching between functions or prehensile types in multiarticulated hand systems or powered transhumeral prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, computer vision methods have been introduced to achieve better accuracy when decoding the users intended action. For instance, researchers have shown that appropriate grasp types can be determined using shape features [33]. Ghazal et al [34] used a deep learning-based artificial vision system which classifies objects with regards to the grasp pattern without explicitly identifying them or measuring their dimensions.…”
Section: Previous Workmentioning
confidence: 99%